Controlling: Between Theory and Practice - Perović, Veselin; Vujičić, Milisav (International Journal of Industrial Engineering and Management, 2015)
Even though controlling as a term dates from the Middle Age, it was accepted by Americans in the 18th century, when a clerk who was responsible for keeping the balance of government budget appears with an official title called comptroller. In the 1970s in Europe, German speaking countries accepted controlling as a more serious topic of conversation. Controlling can be described as a navigation process towards set goals of an enterprise or as an economic consciousness of an enterprise. In German speaking countries, the academic public became interested in controlling right after it was proven to be an effective tool practically. Corporate practice led to the emergence of Controlling in the academic field. In 1960s, positions of controllers started to appear in companies. Around the end of 1960s, the term Controlling was introduced by dr Albrecht Deyhle, who was the most influential person for introducing Controlling to German speaking countries. Because of this of dr Deyhle’s influence, faculties started to research the new phenomenon. The developtment of Controlling as a an academic discipline was driven by a large degree by its positive recognition in business practice. Controling has become a recognized discipline not only in practice, but also in research. An increasing demand for controllers in the business world paved the road for the developtment of Controlling chairs in Germany. In the beginning of 1970s, universities started to offer Controlling courses as a part of business administration degrees. In 1973 the first Controlling chair was established at the Technical University of Darmstadt. In 1974 the second Controlling chair was established at the University of Duisburg. By 1988 there were 14 and by 2004 were 72 chairs for Controlling. Starting in 2005, the course Controlling has been offered to students of specialistic studies at the Faculty of Technical Sciences, University of Novi Sad. Article history: Received (12.11.2015); Revised (20.12.2015); Accepted (29.12.2015)